“Why don’t they participate?” Reasons for nonparticipation in adult learning and education from the viewpoint of self-determination theory - Jan Kalenda; Illona Kočvarová (European Journal for Research on the Education and Learning of Adults, 2022)
The study deals with the perceived reasons for nonparticipation in adult learning and